Teaching in the Suburbs: Participatory Action Research Against Educational Wastage - Parrello, Santa; Iorio, Ilaria; Carillo, Filomena; Moreno, Cesare (Frontiers in Psychology, 2019)
If teaching is a stressful job, it can be even more so in schools in disadvantaged areas, such as the metropolitan suburbs, where the rates of educational wastage are high. Here, teachers often feel ineffective: as a result, there is a reduced sense of well-being at work, which triggers a negative cycle that damages their educational performance. From the literature, it is known that teachers need social support, which has a positive effect on well-being and resilience. For these reasons, the Association ‘Maestri di Strada’ (MdS) has chosen to offer teachers professional social support and to actively involve them through Teacher Participatory Action Research (T-PAR): the ‘Crossing Educational Boundaries’ project. These are the research questions that gave life to the project: do the teachers have resources to analyse the problematic situations they are immersed in and to build improvement strategies? Would a professional social support reinforce their resilience? The objective was the following: to actively engage the teachers in order to generate hypotheses concerning the causes of educational wastage in their schools, and to work with them to plan new methods to lessen the problem. The project was carried out in 12 suburban secondary schools in 6 Italian cities. This paper illustrates the activities of 3 cities. All phases of the T-PAR were completed. The teachers organised discussion groups and started workshops in the classes considered at risk. The activities were subject to non-participant observation, and the observation reports underwent semantic-structural analysis. Four clusters emerged the analysis. The results show that the teachers are aware of the importance of a good educational relationship as a way to oppose educational wastage, and, at the same time, they are aware of the difficulties of building it, which they attribute to the mistrust and passiveness of the pupils, and to the demands of the institution. The moments of discouragement shown by the teachers, and their strong emotional engagement in the pupils’ difficulties are significant. At the end of the project, a small group of teachers planned and implemented a reflective space in some of the schools.